Psychological Impact of COVID-19 Pandemic Among the General Population in Jordan - Khatatbeh, Moawiah; Khasawneh, Aws; Hussein, Hasan; Altahat, Omar; Alhalaiqa, Fadwa (Frontiers in Psychiatry, 2021)
Objective: Pandemics can result in certain stressors. However, the potential psychological impact of the pandemic is often overlooked. This study aimed at assessing the psychological impact of COVID-19 pandemic on Jordanians and to evaluate the influence of the socio-demographic variables on this impact. Method: This was a descriptive cross-sectional study targeting the general population of Jordan via a web-based questionnaire using the Impact of Event Scale-Revised (IES-R). Using convenience sampling, the sample in this study consisted of 2854 participants from the 12 governorates of Jordan. Results: The average score of the participants’ responses on the IES-R questionnaire was 22.5 ± 11.7. Females had more than doubled odds for having increased IES-R score (OR=2.2, CI: 1.76-2.67) and participants who were older than 65 years had triple odds for having the same risk compared to young adults aged 18-25 (OR=3.1, CI: 1.3-7.4). Significantly, having a family member diagnosed with COVID-19 placed individuals at a 7 -fold higher risk of having an increased IRS-R score compared to their counterparts who did not have a family member diagnosed with COVID-19 (OR=7, CI: 3.7-13.3). Conclusion: Governments should collaborate with psychiatrists, mental health professionals, and local institutions to offer high-quality, timely crisis-oriented psychological services to the affected individuals for the duration of the COVID-19 pandemic.